Rejuvenating the gut: young plasma therapy improves cell proliferation, IGF-I and IGF-IR expression, and immune defense in aged male rats jejunum - Asmaz, Ender Deniz; Tan, Murat; Genç, Aysun Inan; Teker, Hikmet Taner; Ceylani, Taha (Springer Science and Business Media LLC, 2025)
Abstract It is well known that aging affects many systems in the body. The digestive system is one of the systems most affected by aging. In our study, we examined the effects of young plasma treatment on cell proliferation, growth factors, immune defense and histological parameters in the jejunum of aged male rats. For this purpose, aged male Sprague Dawley rats (24 months, n = 7) were treated with pooled plasma (0.5 ml/day, intravenously for 30 days) collected from young (5 weeks, n = 51) rats. Aged rats that received young plasma treatment were grouped as the experimental group, while aged rats formed the control group. At the end of the experiment, the jejunums of the groups were collected and histological parameters such as villus height, crypt depth, total mucosal thickness and surface absorption areas were measured and compared. In addition, cell proliferation index and proliferation intensity in the crypt glands of the jejunum were evaluated with proliferating cell nuclear antigen and expressions of growth factors such as insulin-like growth factor I (IGF-I) and its receptor (IGF-IR) expression and effects of immunoglobulin A (IgA), which plays a role in the defense of the digestive system against microorganisms, were examined. In the experimental group, an increase in histological parameters, IGF-R and IGF-IR expression, proliferation density, proliferation index and IgA expression density and IgA cell count were observed compared to the control group. These results suggest that young plasma treatment has a positive effect on the digestive system and may be a potential therapeutic for tissue regeneration.
Keywords: Male; Aging; IGF-IR; Young plasma; Proliferation; IGF-I; Rats; Receptor, IGF Type 1; Immunoglobulin A; Rats, Sprague-Dawley; Plasma; Jejunum; Animals; Insulin-Like Growth Factor I; Intestinal Mucosa; IgA; Research Article; Cell Proliferation